Molecular clocks underlying vertebrate embryo segmentation: a 10-year-old hairy-go-round - Andrade, Raquel P. (2007)
Segmentation of the vertebrate embryo body is a fundamental developmental process that occurs with strict temporal precision. Temporal control of this process is achieved through molecular segmentation clocks, evidenced by oscillations of gene expression in the unsegmented presomitic mesoderm (PSM, precursor tissue of the axial skeleton) and in the distal limb mesenchyme (limb chondrogenic precursor cells). The first segmentation clock gene, hairy1, was identified in the chick embryo PSM in 1997. Ten years later, chick hairy2 expression unveils a molecular clock operating during limb development. This review revisits vertebrate embryo segmentation with special emphasis on the current knowledge on somitogenesis and limb molecular clocks. A compilation of human congenital disorders that may arise from deregulated embryo clock mechanisms is presented here, in an attempt to reconcile different sources of information regarding vertebrate embryo development. Challenging open questions concerning the somitogenesis clock are presented and discussed, such as When?, Where?, How?, and What for? Hopefully the next decade will be equally rich in answers.